Relevansi Pemikiran Ekonomi Al-Ghazali tentang Konsep Uang Penggunaan E-Money sebagai Alat Transaksi Di Era Digital - Juliasari, Diar Eka; Mugiyati (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2026)
This study aims to analyze the relevance of Al-Ghazali's Economic Thought regarding the concept of money in the use of E-money as a transaction tool in the digital era, with a focus on ethical principles and the concept of money in Islamic economics. The study uses a qualitative method based on a literature review approach, as well as literature on Al-Ghazali, especially his works and thoughts and related to e-money and fintech developments. This data was collected through document studies and comparative analysis to compare Al-Ghazali's concept of money with the characteristics of e-money. The results show that Al-Ghazali views money as a medium of exchange and a unit of account that must be free from usury and speculation, which is in line with the function of e-money as an efficient digital transaction medium. However, challenges such as the potential for digital manipulation and non-compliance with sharia principles can reduce its relevance if not properly regulated. The analysis shows that Al-Ghazali's thoughts can serve as an ethical guide for the development of e-money regulations, by emphasizing transparency, fairness, and prevention of economic exploitation. This research contributes to strengthening the Islamic Economic framework in supporting fintech innovation that is in accordance with sharia values.